Efektivitas Pengelolaan Aset Kendaraan di Setda Jombang : Kajian atas Kebijakan Sewa Kendaraan Dinas - Dinda Maura Prameswari; M. Agus Muljanto (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The management of regional assets, especially official vehicles, is an important element in ensuring good and efficient governance. This study aims to evaluate the effectiveness of the official vehicle lease policy at the Regional Secretariat of Jombang Regency, by analyzing it using the view of effectiveness theory according to Duncan in his book Organizational Effectiveness, which focuses mainly on goal achievement, integration, and adaptiveness. The method used is descriptive qualitative, which involves interviews and direct observation. The results of the discussion show that the official vehicle rental policy has succeeded in increasing budget efficiency and operational flexibility, as well as reducing administrative burdens. Good communication between the government and service providers, as well as the use of e-catalogs, support transparency and accountability in procurement. However, challenges related to the transition to electric vehicles still need to be addressed through long-term planning and more in-depth socialization. Overall, while this policy shows significant potential, there is still room for improvement to optimize the effectiveness of official vehicle asset management.